Total haemoglobin mass and red blood cell profile in endurance-trained and non-endurance-trained adolescent athletes - Ulrich, Gert; Bärtsch, Peter; Friedmann-Bette, Birgit (European journal of applied physiology, 2011)
To evaluate differences in total haemoglobin mass (tHb mass) and in red blood cell profile between elite endurance-trained (END) and non-endurance-trained (nEND) male and female adolescent athletes, tHb mass (CO rebreathing) and specific variables of red blood cell profile (haemoglobin concentration, haematocrit, erythrocyte indices) were determined in 59 elite junior athletes (29 END, 30 nEND). We hypothesized that at the age of 15-17 years, regular endurance training might induce a significant increase in tHb mass and changes in red blood cell profile. Therefore, all parameters were again determined after 6, 12 and 18 months in a subset of 27 subjects (17 END, 10 nEND). In END, tHb mass related to body weight was ~15% greater than in nEND (11.2 ± 1.6 vs. 9.7 ± 1.3 g kg−1, P < 0.001), whereas no significant differences were observed for the red blood cell profile. In both groups, tHb mass related to body weight and the variables of red blood cell profile had not changed significantly after 6, 12 and 18 months of regular training. In conclusion, in elite junior athletes, differences in tHb mass between END and nEND were similar, however, smaller compared with previously in adult athletes reported values. At the age of 15-17 years, 18 months of regular training did not induce significant changes in tHb mass beyond alterations explained by physical growth and also variables of red blood cell profile did not change significantly.
Gesehen am 30.11.2022